MONOCEPHALIC TETRABRACHIUS TETRAPUS MONSTER IN A MURRAH BUFFALO - PRASAD, J K; DAS, G K; KRISHNAPPA, B; KUMAR, BRIJESH; RAMTEKE, SNEHAL; RAKESH, H B; SINGH, M; SHARMA, G C; SONI, YOGESH (The Indian Journal of Animal Reproduction, 2023)
A rare case of monocephalic tetrabrachius tetra pus monster was extracted per-vaginally by detruncating in aMurrah buffalo.
Keywords: Monocephalic tetrabrachius tetrapus; Monster; Detruncating; Murrah; Buffalo